Nitrogen Content in Craft Malts: Effects on Total Ester Concentration in Beer. (1st October 2020) - Thompson-Witrick, Katherine A.; Pitts, Eric
Abstract: Malt is an essential ingredient in beer; not only because it provides yeast with essential nutrients such as amino acids and fermentable sugars, it also adds to the beer's color, body and flavor. The objective of this project was to look at the initial concentration of total nitrogen (TN) found within base malts of different varietal and cultivar origins and its impact on the esters produced in beers made using these malts. The experimental beer was brewed with a target OG of 10° Plato wort using five different base malts; four of which were produced by independent craft maltsters (Texas, Oregon, Indiana, and Canada) and a macro-industrial produced malt served as the control. TN and free amino nitrogen (FAN) were analyzed and compared with volatile and semi-volatile flavor analysis in order to identify correlations between nitrogen concentration and ester development within the final beer. One-way ANOVA coupled with a Tukey HSD paired comparison test was run to determine statistical differences in TN and FAN, while Kruskal-Wallis one-way analysis of variance test was utilized to determine statistical differences between total esters production. TN wort values ranged from 627 to 909 mg/L, while FAN wort values ranged from 191 to 467 mg FAN/L. There were statistical differences seen between all of the beers in total ester production. The beers produced with malts of higher TN resulted in greater ester production. From this, one can conclude that there is a correlation between a malt's TN and esters produced in the final beer product.